Competence and Career Development Effects on Service Performance: Motivation Mediation in a Ditlantas BPKB Case Study - Apsari, Kartika Indah Yulia; Anisah, Hastin Umi (Ilomata International Journal of Management, 2026)
This study tests whether officers’ competence and career development improve service performance in the Vehicle Ownership Document (BPKB) unit of the South Kalimantan Regional Police and whether work motivation transmits these effects. Motivated by a documented paradox of high satisfaction scores alongside persistent queueing and responsiveness complaints, we specified a mediation model integrating Human Capital and Public Service Motivation perspectives. A cross-sectional census of 40 frontline officers was analyzed with PLS-SEM. The findings show that higher competence and clearer career development are associated with stronger motivation and better service performance, and that motivation mediates both relationships. The contribution lies in a policing-specific explanation of how capability and career signals translate into outcomes through motivation in a high-functioning yet complaint-prone service. Practical actions include targeted upskilling, mentoring, transparent promotion criteria, and routine feedback and recognition to sustain motivation, improve responsiveness, and shorten queues, thereby aligning resources with demand and strengthening public trust.